Novel Agents For Relapsed and Refractory Classical Hodgkin Lymphoma: A Review - Zhang, Yujie; Xing, Zhichao; Mi, Li; Li, Zhihui; Zhu, Jingqiang; Wei, Tao; Wu, Wenshuang (Frontiers in Oncology, 2022)
Classical Hodgkin lymphoma (cHL) is the most common type of HL that occurs mainly in people aged between 15-30 years and over 55 years. Although its general prognosis is favorable, 10-30% of patients with cHL will ultimately develop relapsed or refractory disease (r/r cHL). It has proven challenging to improve the cure rate of r/r cHL. Some novel agents, such as brentuximab vedotin and immune checkpoint inhibitors, which have been used in conventional regimens for patients with r/r cHL in the past decade, have been shown to have good curative effects. This paper reviews the conventional regimens for patients with r/r cHL and focuses on the newest clinical trials and treatment measures to prolong prognosis and reduce adverse events. The evaluation of prognosis plays a vital role in analyzing the risk of relapse or disease progression; thus, finding new predictive strategies may help treat patients with r/r cHL more efficaciously.